COMPOUND SENTENCE THEORY AND ITS STRUCTURAL AND SEMANTIC TYPES ("XXI ASRDA INNOVATSION TEXNOLOGIYALAR, FAN VA TAʼLIM TARAQQIYOTIDAGI DOLZARB MUAMMOLAR" nomli respublika ilmiy-amaliy konferensiyasi, 2024)
This article explores the theory of compound sentences, focusing on their structural and semantic classifications. Compound sentences, which combine two or more independent clauses, play a vital role in both written and spoken communication. Structurally, they can be linked using coordinating conjunctions, semicolons, or conjunctive adverbs, with variations depending on the writer's intent. Semantically, they are categorized into types such as additive, adversative, causal, alternative, and explanatory, reflecting the relationship between the clauses. The article emphasizes the importance of compound sentences in enhancing clarity, coherence, and expressiveness, making them a fundamental tool in effective language use.